Symbolic diplomacy of place and space in Eurasia: “multi-vector” vs. “third neighbor” policies-impact of nomadic features on foreign policy strategies of Kazakhstan and Mongolia - Campi, Alicia (Turkic Studies Journal, 2021)
This paper examines the present-day diplomatic policies of Kazakhstan and Mongolia, which are two landlocked Eurasian nations that share a common no madic and Soviet heritage. Both utilize symbolism of place and space as intersections between transcontinental subgroupings to promote economic development within a continent dominated by superpower neighbors, China and Russia. The two nations in the democratic era after the collapse of the Soviet Union have devised “Multi-Vector” and “Third Neighbor” strategies derived from their historic nomadic experiences to break out of their landlocked geographical constraints.